The Holy in a pluralistic world Rudolf Otto's legacy in the 21st century - Rosenhagen, Ulrich 1967-; Alles, Gregory D. 1954- (Equinox Publishing Ltd, 2022)
"Rudolf Otto (1869-1937) is widely recognized as one of the most important contributors to the study of religions at the beginning of the 20th century. This book issues an invitation to those with an interest not just in religions but also in cultural phenomena more broadly to take another look at Rudolf Otto and his ideas"--
Includes bibliographical references and index
Keywords: Otto, Rudolf -- 1869-1937; Religionsphilosophie; Otto, Rudolf / 1869-1937; Religion / Philosophy